The synergistic interference effect of silica nanoparticles concentration and the wavelength of ELISA on the colorimetric assay of cell toxicity - Fariba Abbasi (Nature Portfolio, 2021)
Abstract The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay is the most common method for the determination of cell toxicity, but some factors limit the sensitivity of this method, such as pH. Less attention had been paid to the interference effect of optical and plasmonic properties of SiO2 nanoparticles (NPs) in the wavelength range assigned to MTT. This study investigated the synergistic interference effect of SiO2 NPs and wavelength on MTT assay for the first time. The examined variables included the type of SiO2 NPs concentrations (1, 10, and 100 mM) and different wavelengths (470, 490, 520, and 570 nm). The results showed that optical density (OD) increased (p < 0.05) when wavelength and the concentration of crystalline SiO2 NPs increased. So, the maximum OD at 10 and 100 mM were attributed to crystalline SiO2 NPs (p < 0.05) due to the functional group, whereas it was related to amorphous at 1 mM (p > 0.05). According to polynomial regression modeling (PRM), the maximum interference effect was predicted at crystalline SiO2 NPs and wavelength > 550 nm. Besides, the synergistic effects of SiO2 NPs, wavelength, and concentration of NPs had been a good fitting with first-order PRM. Thus, the concentration of SiO2 NPs had a confounder factor in colorimetric for MTT assay. The best artificial neural network (ANN) structure was related to the 3:7:1 network (Rall = 0.936, MSE = 0.0006, MAPE = 0.063). The correlation between the actual and predicted data was 0.88. As SiO2 NPs presence is an interfering factor in MTT assay concerning wavelength, it is suggested wavelength use with minimum confounding effect for MTT assay.